2019
DOI: 10.1177/1533317519826272
|View full text |Cite
|
Sign up to set email alerts
|

Constant Observation Practices for Hospitalized Persons With Dementia: A Survey Study

Abstract: Despite substantial staffing and cost implications, the use of constant observation (CO) has been poorly described in the acute care setting. The purpose of this cross-sectional, multicenter, survey study was to assess hospital provider practices regarding the use of CO. Of the 543 surveys distributed, 231 were completed across 5 sites. Most respondents worked on medical units (67.5%), as nurses (49.1%); 44.8% were white; and 75.6% were female. The majority (84.2%) reported at least 1 patient/wk requiring CO. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 34 publications
(51 reference statements)
0
13
0
Order By: Relevance
“…Notably, participants' knowledge concerning the concept and definition of MH did not improve [1,37] and likewise mental disorders are not rare and afflict those who are genetically vulnerable and have multiple overwhelming stresses including conflicts and wars [9,38]. Most patients with mental disorders do not require hospitalization and special observation as they do not harm themselves or others, and they have abilities to make correct decision about their mental health problems [1,[70][71][72][73]. At global level, MHFA trained participants have benefitted in the following ways; increase knowledge in MH concepts, early recognition of symptoms of mental illness, knowing risk factors of mental illness, early MH seeking pathways, early referral to specialist care, use of early intervention linked with good recovery, reduced stigma and social distance with other favorable attitudes, enhanced confidence in delivering services including utilizing social and family supports to patients with mental illness/ crisis and physical diseases [13,20,25,93,97].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, participants' knowledge concerning the concept and definition of MH did not improve [1,37] and likewise mental disorders are not rare and afflict those who are genetically vulnerable and have multiple overwhelming stresses including conflicts and wars [9,38]. Most patients with mental disorders do not require hospitalization and special observation as they do not harm themselves or others, and they have abilities to make correct decision about their mental health problems [1,[70][71][72][73]. At global level, MHFA trained participants have benefitted in the following ways; increase knowledge in MH concepts, early recognition of symptoms of mental illness, knowing risk factors of mental illness, early MH seeking pathways, early referral to specialist care, use of early intervention linked with good recovery, reduced stigma and social distance with other favorable attitudes, enhanced confidence in delivering services including utilizing social and family supports to patients with mental illness/ crisis and physical diseases [13,20,25,93,97].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported that all patients with mental disorder do not require close surveillance because mostly they do not harm themselves or others and do not require admission [1]. Mentally ill patients, 3% to 20%, especially with severe depression, acute psychosis, substance abuse, borderline personality disorders, dementia, suicidal or homicidal intents, auditory hallucinations and absconding behavior may require admission and special observations [1,[70][71][72]. Regarding 15S, participants' correct (D, 15S) and DKN responses decreased insignificantly (>0.05) and wrong (A, 15S) responses increased significantly (<0.05) means negative impact on trainees' knowledge and practice.…”
Section: Participants Responses To 17 Itemsmentioning
confidence: 99%
“…In hospitals one-to-one specialling is a commonly used strategy for managing the behavioural and psychological symptoms (BPS) experienced by cognitively impaired patients. In a recent multisite survey, 84.2% of nurses reported working with a special at least once a week and at least 60% of these were for agitation in dementia ( Sinvani et al, 2019 ). Cognitive impairment refers to a variety of organic brain syndromes including dementia, delirium, brain injury, and intellectual impairment.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, on medical and surgical wards, rates of patient-to-staff violence are highest in delirium, followed by dementia ( Williamson et al, 2014 ). Hospitals lack validated models of care for managing BPS ( Dewing & Dijk, 2016 ;Digby, Lee, & Williams, 2016 ), and as a consequence, the predominant management strategy has been to rely upon the allocation of an extra staff resource to the patient as a one-toone nurse special ( Moyle, Borbasi, Wallis, Olorenshaw, and Gracia, 2010 ;Sinvani et al, 2019 ;Wood et al, 2018 ). The underlying assumption of specialling is that if a human safety resource is allocated to monitor the patient constantly, falls and other harms may be prevented.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation